Cooked Bones? Method and Practice for Identifying Bones Treated at Low Temperature. (21st March 2013) - Solari, A.; Olivera, D.; Gordillo, I.; Bosch, P.; Fetter, G.; Lara, V. H.; Novelo, O.
Abstract Is it possible to determine low‐temperature cooking in archaeological bones? The indirect exposure of bones to fire at low temperature (≤ 100 °C), linked to cooking, produces macroscopic modifications on these bones. These modifications have not been clearly or systematically described previously. Instead, physicochemical changes at nanometric level are only now beginning to be understood. In this paper, our principle aim is to explore new methods and techniques that correlate macroscopic features such as smoothness or light transparency with physicochemical characterization results that could aid towards detecting cooked bones in the archaeological record. This study then selected 11 archaeological samples, both human and non‐human. Bones were considered to be thermally treated or not, on the basis of macroscopic criteria. Complementary characterization techniques were used to study morphology (scanning electron microscopy and small angle X‐ray scattering), structure (X‐ray diffraction and transmission electron microscopy), local composition (energy‐dispersive X‐ray spectroscopy) and texture (gas adsorption). Indeed, fractal dimension, particle size, crystalline percentage or specific surface area may well explain some of the macroscopically observed modifications on these samples. The possibility that such apparent modifications may also be due to diagenesis is also considered. From an archaeological point of view, the results are promising. Our characterization of human and non‐human bones demonstrates that physicochemical techniques are complementary and provide good criteria against which to distinguish boiled from un‐boiled archaeological samples. Copyright © 2013 John Wiley & Sons, Ltd.